SLA violations reduction for web-based education module in cloud computing education ecosystem. - Ahmad Mosallanejad; Atan, Rodziah; Abdullah, Rusli; Azmi, Masrah (2013)
In cloud computing education ecosystem, service providers are responsible about any violated service level agreements (SLA). Service providers should react against SLA violations which can be happened caused by unpredicted events. A few related works focused on SLA violation reaction which is not compatible for hierarchical cloud computing education ecosystem. This paper proposes a reaction method to prevent and revive the SLA violations within web-based education in cloud computing ecosystem. The proposed method reacts against SLA violations by three strategies including: internal resource reconfiguration, external service invocation, and detected violation propagation. The effectiveness of proposed method is evaluated by stress testing. The experiment results have illustrated that the service provider faced lesser violations by employing the proposed method. This approach further benefits the education ecosystem by providing it with reliable and stabilized platform for learning environment.